The space tourist's handbook where to go, what to see, and how to prepare for the ride of your life - Anderson, Eric.; Piven, Joshua; Tito, Dennis 1940- (Philadelphia, PA Quirk Books, 2005)
Provides practical information for would-be space tourists, describing different types of flights and covering flight training, the launch, emergencies, and such aspects as sleeping in weightless environments and using the vacuum toilet -- Source other than Library of Congress.
Include index.
Keywords: Space tourism -- Popular works; Astronautics -- Popular works; Outer space -- Civilian use -- Handbooks, manuals, etc